THE RELATIONSHIP BETWEEN EDUCATIONAL BACKGROUND AND CAREER DEVELOPMENT (CASE STUDY BANK SULUTGO TONDANO BRANCH) - Melinda, Nainggolan; Pandowo, Merinda (Universitas Sam Ratulangi, 2019)
Educational Background is important for most human resources as well as companies in general. Most companies have set educational background conditions for prospective employees who want to apply for jobs at the company. This study aims to determine whether there is a relationship or there is no relationship between educational background and career development. The study used qualitative methods with data collection techniques using in-depth interview methods. Population this study is employees of Bank SulutGo Tondano Branch. The sample of this studyÂ is 10 respondents. The finding of this research shows educational background and career development are related. Recommended to Bank SulutGo Tondano Branch should continue to monitor the work of each employee to develop their career but not forget and help employees who do not have a college degree but prioritize their abilities, perseverance and personality.Â Keywords: educational background, career development, human resources